2020
DOI: 10.21203/rs.3.rs-115412/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive Effect of Triglyceride‑Glucose Index on Clinical Events In Patients With Type 2 Diabetes Mellitus and Acute Myocardial Infarction: Results From an Observational Cohort Study In China

Abstract: Background: Triglyceride glucose (TyG) index is considered a reliable alternative marker of insulin resistance and an independent predictor of cardiovascular outcomes. However, the prognostic value of TyG index in patients with type 2 diabetes mellitus (T2DM) and acute myocardial infarction (AMI) remains unclear. Methods: A total of 1932 consecutive patients with T2DM and AMI were enrolled in this study. Patients were divided into tertiles according to their TyG index levels. The incidences of major adverse ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Recently, the triglyceride-glucose (TyG) index, measured by the fasting plasma glucose and triglyceride, has been proposed as a reliable surrogate marker of IR and shown to highly correlate with IR [5,6]. Growing evidence has been demonstrated that the TyG index is related to adverse cardiovascular outcomes in the general population [7][8][9], as well as among certain high-risk patients, such as diabetes [10], hypertension [11], myocardial infarction [12], acute coronary syndrome [13], and after percutaneous coronary intervention [14]. In addition, several studies also report a predictive role of the TyG index with adverse cardiovascular outcomes among the general population [7,15] and patients with cardiovascular diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the triglyceride-glucose (TyG) index, measured by the fasting plasma glucose and triglyceride, has been proposed as a reliable surrogate marker of IR and shown to highly correlate with IR [5,6]. Growing evidence has been demonstrated that the TyG index is related to adverse cardiovascular outcomes in the general population [7][8][9], as well as among certain high-risk patients, such as diabetes [10], hypertension [11], myocardial infarction [12], acute coronary syndrome [13], and after percutaneous coronary intervention [14]. In addition, several studies also report a predictive role of the TyG index with adverse cardiovascular outcomes among the general population [7,15] and patients with cardiovascular diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has been demonstrated that the TyG index is related to adverse cardiovascular outcomes in the general population [7][8][9], as well as among certain high-risk patients, such as diabetes [10], hypertension [11], myocardial infarction [12], acute coronary syndrome [13], and after percutaneous coronary intervention [14]. In addition, several studies also report a predictive role of the TyG index with adverse cardiovascular outcomes among the general population [7,15] and patients with cardiovascular diseases [12,13]. However, most of the prior studies mainly focused on older adults with CVD events and mortality, and were inherently limited by short follow-up periods and the use of measured TyG index at a single time point.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the TyG index can predict the occurrence of adverse cardiovascular events in patients with diabetes. [20][21][22] In addition, the TyG index can predict MACE in patients with non-ST-elevation MI. Based on our study, this easy method for identifying IR may optimize the risk stratification of hypertensive patients with a high cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Additionally, other studies have indicated that the TyG index can predict the occurrence of adverse cardiovascular events in patients with diabetes. [20][21][22] Moreover, the TyG index can predict MACE in patients with non-ST segment elevation acute coronary syndrome. 23 However, no studies have focused on the relationship between the TyG index and MACE in patients with HTN.…”
Section: Introductionmentioning
confidence: 99%
“…Being used to detect IR, TyG seems to be cheaper and more convenient than the homeostasis model assessment of insulin resistance (HOMA-IR) index (14). TyG is also associated with cardiometabolic diseasesand is a risk prognostic factor for stroke, diabetes mellitus, acute myocardial infarction and acute coronary syndrome (15)(16)(17). Besides, TyG may be a useful indicator of MAFLD not only in adults but also in children and the elderly(18-20).…”
Section: Introductionmentioning
confidence: 99%